PERANAN INTERNAL AUDIT DALAM PENGAWASAN PIUTANG USAHA PADA CU DAYA LESTARI KABUPATEN KUTAI BARAT - Desna Reti; Martinus Robert Hutauruk; Umar Hi Salim (OBOR: Oikonomia Borneo, 2019)
The formulation of the problem in this study would like to compare the role of internal audit in the control of trade receivables in the Credit Union Daya Lestari in West Kutai barat with Credit SOP (Standard Operating Procedure)? This study aims to determine the role of internal audit in the supervision of trade receivables at CU Daya Lestari West Kutai barat. The benefits of this research as information material for CU Daya Lestari in the role of internal audit Internal audit is an examination carried out by the company's internal parts of the company's financial statements and accounting records. SOP (Standard Operating Procedure) is a guideline or reference in work that is in accordance with the functions and financial requirements in accordance with work procedures, work procedures and work systems that apply in the company. This research method uses a comparative analysis method that is comparing between Supervision of credit or credit or loans according to the SOP (Standard Operating Procedures) in the Credit Union with the conditions that occur in the Credit Union Daya Lestari West Kutai barat. From the results of the analysis, it was learned that the Daya Lestari Kutai Barat Credit Union conducts credit supervision or lending in accordance with the SOP (Standard Operating Procedure) of the Daya Lestari Credit Union. This can be seen from the election table which shows everything is done in accordance with the existing SOP. keywords: internal audit, supervision, accounts receivable, lending, SOP Credit union.